Primary Neuroendocrine Neoplasms of the Breast: Still Open Issues - Gallo, Marco; Campione, Severo; Di Vito, Valentina; Fortunati, Nicoletta; Lo Calzo, Fabio; Messina, Erika; Ruggeri, Rosaria Maddalena; Faggiano, Antongiulio; Colao, Annamaria Anita Livia (Frontiers in Endocrinology, 2021)
Neuroendocrine breast tumors represent a rare subtype of breast cancer, accounting for less than 1% of all neuroendocrine neoplasms. Starting from their pathology definition, and going through their prevalence, prognosis and treatment, our knowledge is still really uncertain. In the present short review of the medical literature on this topic, we have evaluated in details their epidemiology, risk factors, pathogenesis, pathology, clinical presentation, radiographic aspects, prognosis and therapy. We have thus been able to identify a number ofopen issues regarding primary neuroendocrine neoplasms of the breast that need to be clarified. Our ultimate aim was actually to try to understand whether neuroendocrine neoplasms of the breast can be considered a definite clinical entity and if neuroendocrine differentiation of breast tumors has a really clinical relevance.